Earthworms regulate plants' effects on soil microbial nutrient limitations: Examinations with contrasting soils and moisture. (1st March 2023) - Mao, Na; Shao, Ming'an; Wang, Xiang; Wei, Xiaorong
Abstract: Soil microbial nutrient limitations significantly affect microbial processes and thus ecosystem functionality, whereas the response of soil microbial nutrient limitations to earthworms has rarely been addressed but is urgently needed due to the important role of earthworms in terrestrial ecosystems. By examining how earthworms regulate plants' effects on microbial nutrient limitations under contrasting soil types and moisture conditions, we showed that plant presence reduced microbial carbon (C) limitation and such reduction was enhanced by earthworm. Plant presence increased soil microbial phosphorus (P) limitation in soils with earthworms in most cases. Additionally, the effects of plants on microbial nutrient limitations and their responses to earthworms were dependent on soil type (or soil nutrients) and moisture. These results suggested that earthworms have the potential to reduce soil microbial C limitation but enhance P limitation and highlighted the importance of nutrients and moisture in influencing the effects of earthworms and plants on microbial nutrient limitations. Highlights: Earthworms promoted plant growth greatly, especially under nutrient-limited soils. Earthworms regulated the competition between plants and microbes on nutrients. Earthworms reduced soil microbial carbon limitation but enhanced phosphorus limitation.